2014
DOI: 10.1093/rpd/ncu221
|View full text |Cite
|
Sign up to set email alerts
|

Variations of soil radon concentrations along Chite fault in Aizawl district, Mizoram, India

Abstract: The present study concerns measurements of radon emissions from soil carried out during March to July 2013 at Chite fault in Aizawl district, Mizoram, India. In this study, continuous radon monitoring in soil was done by using LR-115 type II nuclear track detector (Kodak-Pathe, France make), and the exposed films were replaced weekly. A negative correlation coefficient (-0.47) between radon concentration and barometric pressure was found during the investigation period. The average radon concentration was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The detectors (LR-115 Films) were cut into a size of 3 cm × 3 cm and loaded in a twin cup radon/thoron discriminating dosimeters, designed and fabricated by Mayya and group (Mayya et al, 1998) at BARC, Mumbai (India). The experimental detail is discussed in Singh et al (2014). The meteorological parameters for the study area were obtained from the IMD-Regional Meteorological Centre, Guwahati, Assam.…”
Section: Experimental Techniques and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detectors (LR-115 Films) were cut into a size of 3 cm × 3 cm and loaded in a twin cup radon/thoron discriminating dosimeters, designed and fabricated by Mayya and group (Mayya et al, 1998) at BARC, Mumbai (India). The experimental detail is discussed in Singh et al (2014). The meteorological parameters for the study area were obtained from the IMD-Regional Meteorological Centre, Guwahati, Assam.…”
Section: Experimental Techniques and Methodsmentioning
confidence: 99%
“…Keeping the above in view, present authors began studies of radon variation as a possible seismic precursor in 2011 at Mat Fault in Mizoram for the first time and the results of this work have been reported (Jaishi et al, 2013;2014a;2014b;). Encouraged with the outcome and for future research, authors extended radon measurement at weekly interval at Chite Fault (Singh et al, 2014). The location of the study area is shown in Fig.…”
Section: Seismicity Of the Study Areamentioning
confidence: 99%
“…Northeast India is seismically one of the six most active regions of the world, the other five being Mexico, Taiwan, California, Japan and Turkey. It lies at the junction of Himalayan arc to the north and Burmese arc to the east [Jaishi et al 2014a, Singh et al 2014]. The high seismicity in this zone is due to the collision tectonics between the Indian plate and the Eurasian plate in the north and Subduction tectonics along the Indo-Myanmar Range (IMR) in the east [Dewey and Bird 1970].…”
Section: Introductionmentioning
confidence: 99%
“…Hence this part has been selected for monitoring of radon anomaly and their possible correlation with the occurrence of earthquakes. Authors have done primary analysis of soil radon and thoron anomalies as a precursor to earthquakes [Jaishi et al 2013, 2014a, 2014b, Singh et al 2014. The present paper describes the multiple regression method to differentiate those radon anomalies which are solely caused by seismic events and not by meteorological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…1 [10]. Correlation of seismic activity with Radon in the region has been studied by Jaishi et al [4,[17][18][19][20] and Singh et al [10,21,22] particularly at Mat fault by Jaishi et al using LR-115 passive system, which lacks the realtime behaviour of Radon during geophysical and non-geophysical processes in the earth crust. In the present study, continuous monitoring, as well as in situ grid-based study, provides a better picture of Radon behaviour at the fault.…”
Section: Introductionmentioning
confidence: 99%